Prediction of fatigue life of semiconductor package under thermal cycling: Combined effect of package design and solder materials - Heon-Su Kim; You-Gwon Kim; Dong-Min Jang; Jin-Woo Jang; Seung-Yeong Lee; Hak-Sung Kim (Materials & Design)
Thermal fatigue tests of semiconductor packages were conducted varying solder materials such as SAC305 and SAC302 with Bi, Ni, and Pd (named hybrid solder ball, HSB) and number of chips inside the package at temperatures ranging from 0 °C to 120°. The fatigue life and fatigue crack types of the solder joint or Cu trace in PCB were monitored by electrical resistance measuring with daisy chain. It was found that the fatigue life and fatigue crack type (solder joint crack or Cu trace crack) were influenced and changed significantly by package geometry and solder joint materials. To predict the crack type and fatigue life of the package, finite element analysis (FEA) was conducted. To analyze the thermal behavior of solder, the creep tests of SAC305 and HSB (SAC302 with Bi, Ni, and Pd) were conducted with respect to temperature and strain rate and their Anand constants were derived. The solder fatigue life was determined using the strain energy-based Morrow’s model, while the Cu trace fatigue life was determined using the strain-based Miner’s model. The predicted fatigue life and crack type from FE analysis agreed well with the experimental results.